SPECT/CT WITH 99MTC-MIBL IN MONITORING OF ESTHESIONEUROBLASTOMA - A. S. Krylov; S. V. Shiryaev; A. D. Ryzhkov; Е. М. Mikhailova; M. O. Goncharov; D. D. Sevryukov (Сибирский онкологический журнал)
This article describes a new approach to the diagnosis of esthesioneuroblastoma. The classical algorithm examination included the whole body 99mTc-MIBI scans and SPECT/CT of the head. There is no data on this method of diagnosis of esthesioneuroblastoma in the scientific literature. A qualitative visualization of the primary tumor and its recurrence after multimodality treatment was reached. SPECT/CT with 99mTc-MIBI is a promising method for detecting esthesioneuroblastoma, however further studies are required.